Risk of Developing Hypokalemia in Patients With Hypertension Treated With Combination Antihypertensive Therapy. Issue 4 (April 2020) - Krogager, Maria Lukács; Mortensen, Rikke Nørmark; Lund, Peter Enemark; Bøggild, Henrik; Hansen, Steen Møller; Kragholm, Kristian; Aasbjerg, Kristian; Søgaard, Peter; Torp-Pedersen, Christian
Abstract : Little is known about the occurrence of hypokalemia due to combination therapy for hypertension. Using data from Danish administrative registries, we investigated the association between different combinations of antihypertensive therapy and risk of developing hypokalemia. Using incidence density matching, 2 patients without hypokalemia were matched to a patient with hypokalemia (K, <3.5 mmol/L) on age, sex, renal function, and time between index date and date of potassium measurement. Combination therapies were subdivided into 10 groups including β-blockers (BB)+thiazides (BB+thiazides), calcium channel blockers (CCB)+renin angiotensin system inhibitors (RASi)+thiazides (CCB+RASi+Thiazides), calcium channel blockers+thiazides (CCB+thiazides), and β-blockers+renin angiotensin system inhibitors+thiazides (BB+RASi+thiazides). We used conditional logistic regression to estimate the odds of developing hypokalemia for different combinations of antihypertensive drugs within 90 days of combination therapy initiation. We matched 463 patients with hypokalemia to 926 patients with normal potassium concentrations. The multivariable analysis showed 5.82× increased odds of developing hypokalemia if administered CCB+thiazides (95% CI, 3.06–11.08) compared with CCB+RASi. Other combinations significantly associated with increased hypokalemia odds were BB+thiazides (odds ratio, 3.34 [95% CI, 1.67–6.66]), CCB+RASi+thiazides (odds ratio, 3.07 [95% CI, 1.72–5.46]), and BB+RASi+thiazides (odds ratio, 2.78 [95% CI, 1.41–5.47]). Combinations of thiazides with CCB, RASi, or BB were strongly associated with increased hypokalemia risk within 90 days of treatment initiation. Abstract : Supplemental Digital Content is available in the text.